Análise gravitacional das exportações interestaduais do Ceará - Carvalho, Jacinta Lucia de (2014)
The present study aims to analyze the trade relations between the state of Ceará and the other States of the Federation of Brazil in the year 2010. The path traced for analysis discusses the technique of the gravitational model as a reference analytical, with a view to develop an empirical model to estimate the determinants of the flow of interstate exports from companies classified in the activity of manufacturing industry. To this end, it was estimated the gravitational model through the Ordinary Least Squares method (OLS) using the commercial transactions of the interstate exports of Ceará, the Gross Domestic Product (GDP) of the states and the distance between Fortaleza and the capitals of other Brazilian states. The data on exports were extracted of the records of the Department of Finance of Ceará (Sefaz-Ce), through the computerized system of electronic invoice (NFE). The empirical results obtained from the analysis indicate that only the variable distance was statistically significant and the signal is in accordance with the provisions in the literature from gravitational models.